Nurses and the National Health Insurance Act of 1995 - Dancel, Maricel Latorilla
The NHIP which is relatively new may need re-evaluation and revision during its implementation process as reflected in findings of similar and relared studies and a few proposals that were dealt with this.~~~~This study was conducted to determine the level of awareness and reactions of nurses regarding the National Health Insurance Act of 1995, associate their level of awareness and reactions with the personal and job-related variables, and see if nurses differ in their views on their roles and chargeable services in the implementation of the National Health Insurance Program of 1995.~~~~A one-group descriptive associational research design was utilized in this study. The study was conducted at the UP-Philippine General Hospital, a tertiary hospital. Sample consisted of nurses from the Department of Pay Patient Services and Charity Wards.~~~~In addressing the identified research problems, conclusions were drawn based on the findings. Nurses have moderate level of awareness on all most all of the salient features and contents of the National Health Insurance Act and Program. However, findings show that they have little awareness on the benefits derived from the program and services that are not covered by it.~~~~Findings showed that extent of awareness of nurses on the NHIA of 1995 is associated with educational background, family needs, job position and area of assignment. Moreover, views of the nurses on their roles in the implementation of the NHIP are associated with age, civil status, sex, religion, educationalbackground, history of confinement and availment of health insurance benefits, job position and number of years in the service.~~~~Although the study was able to point out significant relationships among the independent and intermediate and dependent variables, comprehensive and broad generalizations cannot possibly be drawn due to other factors that may ...